2021
DOI: 10.1007/s40261-021-01010-z
|View full text |Cite|
|
Sign up to set email alerts
|

Amikacin Liposome Inhalation Suspension in Refractory Mycobacterium avium Complex Lung Disease: A Profile of Its Use

Abstract: Amikacin liposome inhalation suspension (ALIS) [Arikayce ® Liposomal (EU); Arikayce ® (USA)], a liposomal suspension of the aminoglycoside amikacin (590 mg) for nebulization via the Lamira ® Nebulizer System, is available as add-on therapy for treatment-refractory Mycobacterium avium complex (MAC) lung disease in adults who have little or no alternative treatment options. Its addition to guideline-based therapy (GBT) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The recommended dosage of ARIKAYCE ® in adults is once daily or one 590 mg amikacin/8.4 mL ARIKAYCE ® vial. It is simple to administer, as follows: mixing the vial contents thoroughly, pouring the contents into the reservoir of the nebulizer handle, and finally starting the nebulizer for inhalation [ 153 , 154 ].…”
Section: Vibrating Mesh Nebulizers Are Suitable For Inhalable Nano-fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended dosage of ARIKAYCE ® in adults is once daily or one 590 mg amikacin/8.4 mL ARIKAYCE ® vial. It is simple to administer, as follows: mixing the vial contents thoroughly, pouring the contents into the reservoir of the nebulizer handle, and finally starting the nebulizer for inhalation [ 153 , 154 ].…”
Section: Vibrating Mesh Nebulizers Are Suitable For Inhalable Nano-fo...mentioning
confidence: 99%
“…The formulation for ARIKAYCE ® consists of amikacin sulfate encapsulated in liposomes at a targeted concentration of 70 mg amikacin/mL, with a pH range of 6.1–7.1 and lipid–amikacin weight ratio in the range of 0.60–0.79. Inactive components include cholesterol and dipalmitoylphosphatidylcholine (DPPC), the lipid materials of liposomes, as well as sodium chloride to regulate osmolality, sodium hydroxide to regulate pH, and water for injection as a solvent [ 153 , 154 ]. Overall, the formulation for ARIKAYCE ® is relatively simple and only consists of common pharmaceutical excipients, which is consistent with the idea that excipients for nebulized formulations are simpler and safer, as we mentioned above.…”
Section: Vibrating Mesh Nebulizers Are Suitable For Inhalable Nano-fo...mentioning
confidence: 99%
“…Amikacin is an aminoglycoside drug that achieves antibacterial effects by interfering with the synthesis of bacterial proteins. It penetrates the biofilm of Mycobacterium avium complex and exerts strong antibacterial activity in vitro [80,81]. ALIS has been prepared by mixture of 70 mg/mL of amikacin dissolved in water with lipids (dipalmitoylphosphatidylcholine and cholesterol) dissolved in ethanol at a specific flowrate ratio.…”
Section: Liposomesmentioning
confidence: 99%
“…Despite that, no inhaled TB treatment has made it to the market yet. It is worth noting that in 2018, the FDA approved the first nebulised amikacin liposome inhalation suspension for Mycobacterium avium complex (MAC) ( Hoy, 2021 ). A phase I clinical trial of capreomycin dry powder formulation for drug resistant TB, demonstrated safety in healthy adult volunteers ( Dharmadhikari et al, 2013 ).…”
Section: Formulation and Delivery Strategies For Atramentioning
confidence: 99%